ADJUSTMENT OF GENDER IDENTITY AND CONSEQUENCES ON EMPLOYMENT RIGHTS: 1. УВОДНА РАЗМАТРАЊА 2. ИМПЛИКАЦИЈЕ МЕДИЦИНСКО - ПРАВНЕ ПРОЦЕДУРЕ ПРИЛАГОЂАВАЊА РОДНОГ ИДЕНТИТЕТА НА СТАТУС И ПОЛОЖАЈ ТРАНСИДЕНТИТЕТА 2.1. Последице прилагођавања родног идентитета на права из радног односа Закључна разматрања - Perić, Slobodanka P (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
The gender identity of every person represents an integral part of their personality and belong to one of the basic aspects of self-definition, dignity and freedom. A certain number of people do not identify themselves with the sex allotted to them at birth, a problem arising regarding their inner comprehension of gender (self-defining), which does not correlate to the sex. Those people are called trans people. In this paper, the author examines the position of trans people i.e. individuals of different gender identity through the prism of the realization and protection in the field of labour rights and the rights arising from employment. Тrans people belong to one of the most vulnerable (most discriminated) groups within society – discrimination is most evident in case of seeking a work placement and during employment, while the key performers are the state and its institutions. It could be said that conditioning and interdependence between the legal procedure of adjustment of gender identity and medical interventions, leave the legal and life status of a transgender person in “vacuum”, which leads to the situation of gender identity being the grounds for further transphobia and discrimination of transgender people in all the aspects of human rights realization. However, in the procedure of further adjustment of gender identity, a transgender person can be registered in the birth certificate register, they can change their personal documents only based on the certificate of a health institution that they have been through a psychological check-up and a year-long hormone therapy prescribed by an endocrinologist. In practice, such regulations put “on hold” the personal status of a transgender person, which leads to the discrimination of transgender people based on gender identity, especially in the phase of transition, when the changes are visible but non-compliant with the sex verified in personal documents. Therefore, it is crucial that, instead of partial amendments to certain laws, an umbrella law (lex specialis) be adopted - Law on Gender identity.